Eliminating Schistosomes through Vaccination: What are the Best Immune Weapons? - Fonseca, Cristina Toscano; Oliveira, Sergio Costa; Alves, Clarice Carvalho (Frontiers in Immunology, 2015)
The successful development of vaccines depend on the knowledge of the immunological mechanisms associated with the elimination of the pathogen. In the case of schistosomes, its complex life cycle and the mechanisms developed to evade host immune system, turns the development of a vaccine against the disease into a very difficult task. Identifying the immunological effector mechanisms involved in parasite attrition and the major targets for its response is a key step to formulate an effective vaccine. Recent studies have described some promising antigens to compose a subunit vaccine and have pointed to some immune factors that play a role in parasite elimination. Here we review the immune components and effector mechanisms associated with the protective immunity induced by those vaccine candidates and the lessons we have learned from the studies of the acquired resistance to infection in humans. We will also discuss the immune factors that correlate with protection and therefore could help to evaluate those vaccine formulations in clinical trials.